CHEMICAL COMPOSITION AND IN VITRO RUMINAL FERMENTATION CHARACTERISTIC OF SONNERATIA ALBA - Dian Agustina; Takdir Saili; Nursanty Asminaya (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
The aim of study was to determine chemical composition and comparison of nutritive value of Sonneratia alba and other forages (Gliricidia sepium and Leuchaena leucochepala) by using in vitro gas production technique. The result showed crude protein content in S. alba was lower than that G. sepium (p<0.05) and L. leuchochepala. The NDF content among treatments non significant difference. The ADF and lignin content S. alba were the highest. VFA production and dry matter degradability of S. alba comparable with G. sepium and L. leuchocepala.The ammonia-N production S. alba higher than G. Sepium but showed lower than L. leuchocepala. In conclusion, according to the chemical composition Sonneratia alba was a high-quality feed resources. Utilization of Sonneratia albaby ruminal microorganism in vitro was available. Further in vivo studies could be required to expand the knowledge of the nutritive value Sonneratia alba.